PENGARUH FAKTOR PENGETAHUAN DAN PETUGAS KESEHATAN TERHADAP KON SU MSI OB AT KAK I GAJ AH (FI L ARI ASI S) DI KELURAHAN BLIGO KECAMATAN BUARAN KABUPATEN PEKALONGAN - Imam Purnomo; Supriyo .; Sri Hidayati (LPPM Universitas Pekalongan, 2015)
Filariasis or elephantiasis disease in Indonesia is widespread throughout the province. This disease does not cause death , but it can result in lifelong disability , social stigma , as well as psychosocial barriers resulting in lower work productivity of patients , families and communities who cause huge economic losses . Pekalongan is one of the endemic areas of filariasis cases the number is increasing year by year with the number of microfilariae ( mf ) rate of 1 % or more . Subdistrict Buaran is one of filariasis endemic areas with the highest rate Mf of 3.9 % . Filariasis mass drug administration strategy is to break the chain of transmission of filariasis by mass prevention approach to all residents of filariasis -endemic areas . And the Village Bligo ranks lowest in drug delivery elephantiasis among Rural / Urban Village in the District Buaran . Based on such information , the author is very interesting to do research on the factors associated with the consumption of drinking drug elephantiasis ( filariasis ) in the Village Bligo Pekalongan .This research is an explanation (explanatory research) through hypothesis testing with survey method using questionnaires and interviews with a cross-sectional approach. Based on the survey results revealed there are significant effect knowledge of drug consumption elephantiasis with p-value of 0.001 , and there are significant effect health workers against elephantiasis drug consumption in Sub Bligo Pekalongan with p -value of 0.011.Suggestions in this research is to TPE officers are there in the Bligo Village expected to increase the dissemination of elephantiasis drug that increases Bligo Village community achievement elephantiasis drug consumption by always giving an understanding of the benefits of the drug when distributing drugs elephantiasis elephantiasis.Keywords: filariasis, mass elephantiasis drug consumptionBibliography: 16 Books (years 1994-2010)